Analisis Persepsi Masyarakat Mengenai Fungsi Uang Perspektif Ekonomi Islam - Nola Adilla; Aidil Alfin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the perspective of Islamic economics, there are only 2 functions of money, namely money as a unit of value and money as a medium of exchange. There are 4 functions of money in a conventional economic system, namely money as a unit of account, money as a unit of exchange but in a conventional economic system, money does not only function as a valid medium of exchange but also as goods that can be traded or to make a profit, money as a storage unit. value, money as the standard unit of payment in the future. This study aims to find out how the perceptions of the Bukittinggi community regarding the function of money from an Islamic economic perspective. The type of research used is descriptive qualitative research. The research informant is the Muslim community of Bukittinggi City. Data collection is done by documentation, observation and interviews. The data analysis technique used is data reduction, data presentation, and drawing conclusions. From the results of research conducted by researchers, it was found that most people's perceptions about the function of money are in line with Islamic economics, but a small number have perceptions that are not in line with Islamic economics because they think that money can be used as a tool for personal gain. This is contrary to the concept and function of money in Islam.